Suburban dicks - Nicieza, Fabian (G.P. Putnam's Sons, 2021)
The cocreator of Deadpool presents this highly entertaining debut novel that follows a very pregnant former FBI profiler as she, with her five kids in tow, tries to solve the murder of a gas attendant with the help of a disgraced local journalist.